(3TQM (B( (3cJGH (B) (3GdKeQIs - (3CHh LYaQ CMeO Hf jhSa Hf EHQGgje GdHZOGOj GdeUQj GHf GdOGjIs; (3HWdjehS GdMcje GdbdhPjs ((3eOjfI GdQi s)
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf hHYO agPG cJGH KeQI HWdjehS GdMcje ef KeGQ GdcJH GdCQHYI cdeI CbGd HWdjehS Yde GdfLhe efc hefgG s
(3BNQgG (B:s
(3agPG eG MVQfi ef JaSjQ cdeGJ gPG GdcJGH hCQLh Cf jchf eMjWkG HeYGfjg eSJhajkG dTQMg Je cJGH HWdjehS GdeSei GdKeQI hGdMeO ddg s
(3fSNI KGfjI ChdgG NGd ef ebOeI GdTGQM GdehLhOI ai GdfSNI GdChdi ceG JfbU efgG GdhQbI GdKGfjIs
(3jJab BNQgG eY BNQ GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B229 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3edi edc (B_ (3WgQGf (B(5924) s
Keywords: (3Gdadcs